Qualitative research in nursing : advancing the humanistic imperative - Streubert, Helen J.; Carpenter, Dona Rinaldi (Philadelphia, Pennsylvania : Wolters Kluwer, 2011)
The fifthe edition of this popular and informative text provides step-by-step guidance to understand and implement successful qualitative research methods in the world of contemporary nursing. This new edition offers for the first time a test generator with NCLEX-style questions and PowerPoint slides online at the Point.
Chapter 1 : Philosophy and theory : foundations of wualitative research -- Chapter 2 : The Conduct of qualitative research : common essential elements -- Chapter 3 : Designing data generation and management strategies -- Chapter 4 : Ethical considerations in qualitative research -- Chapter 5 : Phenomenology as method -- Chapter 6 : Phenomenology in practice, education, and administration -- Chapter 7 : Grounded theory as method -- Chapter 8 : Grounded theory in practice, education, and administration -- Chapter 9 : Ethnography as method -- Chapter 10 : Ethnography in practice, education, and administration -- Chapter 11 : Historical research method -- Chapter 12 : Historical research in practice, education, and administration -- Chapter 13 : Action research method -- Chapter 14 : Action research method -- Chapter 15 : Triangulation as a qualitative research strategy -- Chapter 16 : Writing a qualitative research proposal -- Chapter 17 : A Practical guie for sharing qualitative research results
Includes bibliographical references and index.
Keywords: NURSING -- RESEARCH -- METHODOLOGY